Introduction of Loose Part Media as an Effort to Increase the Creativity of Children Aged 5-6 Years: A Qualitative Study in Early Childhood Education - Khoirunnisa, Sindi Rahma; Fauziyah, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to examine the concept of using loose part media for children's freedom in creativity, as well as its benefits for the development of children's creativity. As well as identifying the advantages and disadvantages in the implementation of the loose part method in learning. Methodology: This study uses a qualitative descriptive method with data collection techniques based on observation, interviews and documentation The research subjects involved teachers and group B children at Aisyiyah Pucangan Kindergarten. Results: The results of the research show that the Loose Parts method can be a very effective tool in increasing children's creativity, but keep in mind that its use must be done with several considerations, its application needs to be done appropriately to maximize the benefits and avoid shortcomings. Applications/Originality/Value: Loose parts media have a very positive impact on learning in PAUD because of its loose nature and easy to get in the surrounding environment and its many varieties make it easier for teachers to provide it for student learning media. Loose parts media provide new innovations in learning in PAUD because it can improve students' thinking skills, both critical thinking skills, creative thinking skills.